Intergenerational Transfers and Liquidity Constraints - Cox, Donald (Quarterly Journal of Economics, 1990)
A growing body of evidence indicates that liquidity constraints could affect a substantial proportion of U. S. consumers, but little is known about why these constraints might exist. An important, but little-explored, issue is the relationship between inter vivos intergenerational transfers and liquidity constraints. These transfers can ease borrowing constraints. Empirical transfer patterns match those predicted from a model in which transfers are allocated to liquidity-constrained consumers. In particular, the distinction between current and permanent incomes of potential recipients is a key aspect of private-transfer behavior. The findings have important implications for our understanding of consumer behavior.